2016
DOI: 10.1007/s10620-016-4184-4
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects Oxidative Stress-Induced Intestinal Epithelial Barrier Dysfunction by Upregulating Heme Oxygenase-1 Expression

Abstract: Res protected gut barrier function possibly by initiating HO-1-dependent signaling which is essential for common expression of key tight junction proteins. It also provides a rationale to develop Res clinical applications of intestinal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 51 publications
3
64
0
2
Order By: Relevance
“…an important topic in the current medical field 42,43) , studies have shown that ischemic stroke can cause an increase in intestinal barrier permeability [44][45][46] . Whether in morphological observation or protein level detection, the intestinal barrier of the Model group was destroyed and the permeability was enhanced.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…an important topic in the current medical field 42,43) , studies have shown that ischemic stroke can cause an increase in intestinal barrier permeability [44][45][46] . Whether in morphological observation or protein level detection, the intestinal barrier of the Model group was destroyed and the permeability was enhanced.…”
Section: Biological and Pharmaceutical Bulletin Advance Publicationmentioning
confidence: 99%
“…In the same study, resveratrol increased glutamate cysteine ligase mRNA expression and the ratio of reduced GSH/oxidized GSH (GSSG) and decreased reactive species production. Resveratrol has also been shown to promote hemoxygenase‐1 (HO‐1) expression in vitro and in vivo ; HO‐1, a cytoprotective enzyme against oxidative stress, could possibly interfere with the expression of iNOS and consequent production of NO to ameliorate experimentally induced colitis …”
Section: Beneficial Effects Of Resveratrol On Therapy For Ibdmentioning
confidence: 99%
“…Although the precise inhibitory mechanism of the disruption of intestinal barrier function is still unclear, the possible explanation is that 5‐ALA/SFC directly up‐regulate ZO‐1 expression. In the previous reports, HO‐1 was involved in the regulation of tight junction proteins in oxidative stress–induced endothelial barrier dysfunction such as intestinal epithelial dysfunction (Chi et al., ; He et al., ; Sivasubramaniyam et al., ; Wang et al., , ), blood–spinal cord barrier (Yu et al., ), and pulmonary barrier (Xie et al., ). Additional possibility is regulatory mechanism of cytochrome P450 2E1 (CYP2E1) expression by 5‐ALA/SFC.…”
Section: Discussionmentioning
confidence: 96%